Average Consensus Analysis of Distributed Inference with Uncertain Markovian Transition Probability. (20th November 2013) - Kim, Won Il; Xiong, Rong; Zhu, Qiuguo; Wu, Jun
Abstract : The average consensus problem of distributed inference in a wireless sensor network under Markovian communication topology of uncertain transition probability is studied. A sufficient condition for average consensus of linear distributed inference algorithm is presented. Based on linear matrix inequalities and numerical optimization, a design method of fast distributed inference is provided.